Non-AIDS-defining illnesses and causes of death in HIV-infected patients in St. Petersburg and Leningrad Region - Z. M. Zagdyn; G. V. Volkova; A. G. Rachmanova; A. Yu. Kovelenov; R. Heimer (Журнал инфектологии)
With the aim of an evaluation of the prevalence of non-AIDS-defining illnesses and causes of death in HIVinfected patients 111 medical records of subjects admitted to the specialized hospitals in St. Petersburg in 2001–2008,were analyzed retrospectively. The most frequent non-AIDSdefining illnesses in HIV-infected patients in the era of the absence of the systematical antiretroviral therapy are gastrointestinal diseases. HIV-infected patients mostly die from generalized tuberculosis and chronic viral hepatitis at the End-Stage liver cirrhosis. To properly evaluate the preavalnce of Non-HIV-related diseases and causes of death in HIV-infected people in St. Petersburg and Leningrad region we need to conduct prospective cohort study in comparison with general population.